Long‐Term Cognitive Prognosis of Profoundly Deaf Older Adults After Hearing Rehabilitation Using Cochlear Implants. Issue 8 (8th August 2018) - Mosnier, Isabelle; Vanier, Antoine; Bonnard, Damien; Lina‐Granade, Geneviève; Truy, Eric; Bordure, Philippe; Godey, Benoit; Marx, Mathieu; Lescanne, Emmanuel; Venail, Frédéric; Poncet, Christine; Sterkers, Olivier; et al.
Abstract : Objectives: To analyze long‐term cognitive status and function after cochlear implantation in profoundly deaf individuals. Design: Prospective observational longitudinal study. Setting: Ten academic medical centers referent for cochlear implantation. Participants: Individuals aged 65 and older who qualified for cochlear implantation (N=70). Measurements: Cognitive tests were administered before cochlear implantation and 1 and 5 or more years after cochlear implantation. Evaluation consisted of 6 tests assessing attention, memory, orientation, executive function, mental flexibility, and fluency. Cognitive status was determined as normal, mild cognitive impairment (MCI), or dementia. Speech perception in quiet and noisy conditions was assessed using disyllabic words, and quality of life was assessed using the Nijmegen Cochlear Implant Questionnaire. Results: Mean follow‐up was 6.8 years (range 5.5–8.5 years). Speech perception scores and quality of life remained stable from 1 to 7 years after cochlear implantation. Of 31 participants (45%) with MCI before cochlear implantation, 2 (6%) developed dementia during follow‐up, 19 (61%) remained stable, and 10 (32%) returned to normal cognition. None of the 38 with normal cognition developed dementia during follow‐up, although 12 (32%) developed MCI. Conclusion: MCI is highly prevalent in older adults with profound hearing loss. Nevertheless, we observed a low rate of progression to dementia, and cognitive function improved in some individuals with MCI at baseline. These results highlight that cochlear implantation should be strongly considered in profoundly deaf individuals, even those with MCI, who may have a specific subtype of MCI, with a possible positive effect of hearing rehabilitation on neurocognitive functioning.